Efeitos do tabagismo passivo no tranporte mucociliar e sistema nervoso autônomo de adultos - Freire, Ana Paula Coelho Figueira [UNESP] (2015)
It is known that the impairment caused by smoking can be extended to passive smokers. There are still gaps regarding the damages of passive smoking on mucociliary clearance and autonomic nervous system. Also, is not known the influence of the frequency and duration of exposure to cigarette smoke in these systems. Therefore policies are needed to reduce the risks of passive exposure, such as encouragement to smoking cessation programs, which can cease the exposure to cigarette smoke. Objective: To evaluate the effect of passive smoking on mucociliary clearance and the autonomic nervous system and investigate possible alternatives to enhance the treatment of smoking cessation. Methods: We evaluated three groups: active smokers (SG) (n = 44), passive smokers (PSG) daily exposed to cigarette smoke (n = 38) and subjects in control group (CG) (n = 38). Initially we performed initial assessment and evaluation of lung function. Then, for analysis of the autonomic nervous system, we collected heart rate variability data (HRV) by heart rate monitor in rest for 20 minutes. Hemodynamic parameters and carbon monoxide in exhaled air were measured. Then, mucociliary clearance was evaluated using the saccharin transit time test (STT). For analysis of new procedures in a smoking cessation program, the following actions were implemented: increasing the frequency of meetings; date of smoke cessation preset by the program therapists, first meeting with presentation of the treatment, clarify doubts and patient motivation and participation of former smokers to encourage beginners...